A Novel Tyrosinase Gene Plays a Potential Role in Modification the Shell Organic Matrix of the Triangle Mussel Hyriopsis cumingii - Ren, Gang; Chen, Chao; Jin, Yefei; Zhang, Genfang; Hu, Yiwei; Shen, Wenying (Frontiers in Physiology, 2020)
Although tyrosinases were speculated to participate in the shell formation of molluscs, there is still lack experimental evidence to support this assumption. In this study, a novel tyrosinase designated HcTyr2 was isolated and characterized from the freshwater mussel Hyriopsis cumingii. The change in HcTyr2 mRNA expression during the process of embryonic development was detected by real-time quantitative PCR. The result showed that the expression of HcTyr2 mRNA was significantly upregulated at the stages of gastrulae and unmatured glochidia (P < 0.05), suggesting that this gene might fundamentally participated in the biogenesis and growth of the initial shell. Meanwhile, the upregulation of HcTyr2 mRNA at the stages of shell regeneration, 24 h and 9 d after shell notching in mantle edge (P < 0.05) implied that it might play an important role in shell periostracum and nacre formation by mediating the cross-linking of quinoproteins to promote the growth and the subsequent maturity of organic matrix. Additionally, the knockdown of HcTyr2 mRNA by RNA interference resulted in not only the suppression of periostracum growth but also the structure disorder of nacre aragonite tablets detected by scanning electron microscopy. These results suggested that HcTyr2 might regulate the growth of shell by its oxidative ability to transform soluble matrix proteins into insoluble matrix proteins, then to promote the maturity of shell organic framework in H. cumingii. In general, our results suggested the important of HcTyr2 in shell formation and regeneration of H. cumingii.